Kualitas Daun Binahong (Anredera cordifolia) pada Suhu Pengeringan Berbeda - Hesti Fajar Utami; Rini Budi Hastuti; Endah Dwi Hastuti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2015)
Binahong leaf is one of the plants that can be used as a traditional medicine. An important step in the use of leaf binahong as drugs is by drying. This study aims to determine the effect of different drying temperature treatment on quality of leaf binahong. The research is divided into two stages: 1. to investigate binahong leaf quality of weight loss changes, the color and texture of the leaves binahong after different drying; 2. to investigate flavonoid quality changes after different drying. The study design used was completely randomized design (CRD) with one factor, namely the factor of temperature drying 270C,300C temperature, the temperature of 400C and 500C temperature for 1 day. The parameters of this study consisted of weight loss percentage, percentage of water content, leaf color, leaf texture and flavonoid content analysis. Analysis of the data used isAnalysis of Variance (ANOVA) followed by Duncan's real different test at 95%significance level. The results showed that the drying temperature tends to increase the rate of weight loss, eliminating moisture, affect change in color and texture of the leaves and reduce the content of flavonoids. Drying temperature 500C showed the best results in reducing weight loss and moisture content, but is not able to maintain the color and texture of the leaves and leaf flavonoid content binahong, while the temperature of 270C, a temperature of 300C and 400C temperature is able to maintain the color and texture of the leaves but slightly lowers weight loss and levels water. The highest binahong leaf flavonoid produced at a temperature of 270C is equal to 10,729% followed by a temperature of 300C at 1,305%, 0,753% temperature of 400C and 500C temperature of0,651, so it is recommended to use as a traditional medicine, the leaves should be consumed directly binahong. Keywords: Anredera cordifolia, drying temperature, flavonoid